'A Convulsed and Magic Country': Tourism and Resource Histories in the Mexican Caribbean. (1st February 2005) - Redclift, Michael
Abstract : Much of the discussion of 'space' in the recent literature has been concerned to provide a more 'active' account of its role in the transformation of historical epochs. Geographical frontiers, for example, are ascribed figuratively, temporally and spatially in ways that serve to influence succeeding events. Their 'discovery' is acknowledged as an element in powerful myths, which are reworked to create environmental histories as important as the material world they describe. This article takes as an example the Mexican Caribbean, which has recently been 'discovered' as a location for mass tourism and whose early tourist 'pioneers' are beginning to be celebrated in the region. It argues that far from having been an empty space, much of the area currently devoted to tourism once played an important role within global markets, especially through the production of dyewoods, chicle (the original raw material for chewing gum) and other natural resources. The paper concludes that discourses of space can be divided into three phases, the 'analogue', the 'digital' and the 'virtual', each of which contributes to a mythology of succession.